Pseudo-boehmite, preparation method thereof and gamma-alumina carrier with high diffusion mass transfer performance

By adjusting the reaction conditions in the double aluminum method, a quasi-thin alumina with high regulation flexibility was prepared, which solved the problem of poor pore size distribution regulation flexibility in the prior art, and achieved a γ-alumina support with high diffusion mass transfer performance, meeting the needs of different catalytic reactions and improving the efficiency of the catalytic reaction.

CN119612563APending Publication Date: 2025-03-14CHINA UNIV OF PETROLEUM (BEIJING)

Patent Information

Application Number
CN202411762752.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing double-aluminum method has poor pore size distribution regulation flexibility, which is difficult to meet the demand for the carrier pore structure of different catalytic reactions and affects the mass transfer and diffusion ability of the catalyst.

Method used

By changing the limited reaction conditions, including preheating, batch-coupling and step-by-step temperature-changing aging, the pH value of the gel-forming reaction is controlled to be between 5.0 and 8.5, a phthalinated alumina with high regulation flexibility was prepared, thereby obtaining a γ-alumina carrier with high diffusion mass transfer performance.

Benefits of technology

Flexible regulation of the phthal-thin water-aluminum stone pore structure is achieved, the pore permeability and diffusion performance of γ-alumina support is improved, the needs of different catalytic reactions are met, and the efficiency and selectivity of catalytic reactions are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612563A_ABST
    Figure CN119612563A_ABST
Patent Text Reader

Abstract

The invention provides pseudo-boehmite, a preparation method thereof and a gamma-alumina carrier with high diffusion mass transfer performance. The preparation method comprises the following steps: respectively preheating an aluminum-containing acidic solution, a sodium metaaluminate solution and reaction bottom water to gel forming reaction temperature; under stirring, dropwise adding the first part of the aluminum-containing acidic solution and the first part of the sodium metaaluminate solution into the reaction bottom water, controlling the pH value of the gelling reaction to be 5.0-8.5, and uniformly mixing to obtain material slurry; dropwise adding all the residual aluminum-containing acidic solution and the residual sodium metaaluminate solution into the material slurry, and carrying out gel forming reaction to obtain reaction slurry; and carrying out step-by-step variable-temperature aging on the reaction slurry, and carrying out suction filtration, washing and drying to obtain the pseudo-boehmite. According to the method, the problem of poor pore regulation flexibility in a traditional double-aluminum method is solved, the limitation of the pore size can be overcome, and the pore permeability of the gamma-alumina carrier is improved, so that the diffusion mass transfer performance of the gamma-alumina carrier is greatly enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic chemical material synthesis, and specifically relates to pseudo-boehmite and a preparation method thereof and a gamma-alumina carrier with high diffusion and mass transfer performance. Background Art

[0002] Different catalytic reactions have different requirements for the pore structure of the catalyst, and the pore structure of the catalyst is determined by the pore structure of the carrier. Therefore, controlling the preparation process of the precursor pseudo-boehmite to regulate the pore structure of pseudo-boehmite becomes an important step in catalyst preparation.

[0003] Specifically, the performance of hydroprocessing catalysts depends not only on the active components, but also on the coordination between the active components and the carrier. The specific surface area of ​​the carrier directly affects the loading amount and dispersion performance of the active components, while the size of the pore volume and the pore size distribution affect the accessibility of the active center and the mass transfer efficiency. Therefore, the performance of the carrier is crucial to the effective performance of the catalyst activity and stability.

[0004] Among many catalyst carriers, alumina is a high value-added inorganic chemical material with many excellent physical and chemical properties. It is widely used in oil processing and Fischer-Tropsch synthesis. The preparation methods of its precursor pseudo-boehmite include carbonization method, alcohol aluminum method, hydrothermal synthesis method and double aluminum method. At present, the industry mostly uses carbonization method and double aluminum method to produce pseudo-boehmite. However, due to the problems of small specific surface area and pore volume of pseudo-boehmite products synthesized by carbonization method, it is difficult to meet the current demand for catalyst carrier pore structure when processing heavy and inferior raw oil. In addition, in the process of preparing pseudo-boehmite, the properties of the obtained product are often different from those of the target product due to uneven mixing of reactants. Therefore, the double aluminum method, which has a series of advantages such as mature technology, low production cost, simple production operation flow and less pollution, has become the first choice.

[0005] At present, the types and demands of raw materials in petroleum processing are undergoing major changes, and it is necessary to process raw material molecules of various sizes. Since the pseudo-boehmite products prepared by the double aluminum method have poor flexibility in adjusting the pore size distribution, the traditional double aluminum method is gradually unable to meet the different requirements of the pore structure of the catalyst carrier. In addition, in the hydrogenation catalytic reaction, the mass transfer and diffusion capacity of the hydrogenation catalyst carrier will directly affect the effective contact and reaction rate between the catalyst and the reactants, thereby affecting the efficiency and effect of the entire catalytic process. Therefore, it is of great significance to study and develop the high diffusion and mass transfer performance of the carrier.

[0006] CN102173442B discloses a method for preparing alumina with adjustable pore size. The method dissolves n-butanol or cyclohexane in bottom water by high shear emulsification, dissolves an appropriate amount of dispersant in the reaction raw materials aluminum sulfate and sodium metachlorite solution by emulsification, and then adds the raw materials into the bottom water twice in parallel to make them fully react; the slurry after the reaction is aged and then filtered and washed to obtain a pseudo-boehmite filter cake, and the pseudo-boehmite and an appropriate amount of organic solvent and dispersant are subjected to atmospheric distillation of the emulsion obtained by high shear emulsification; finally, it is dried, heated and roasted, and the dispersant is removed to obtain alumina powder. CN101412527B discloses a method for preparing mesoporous alumina powder with adjustable pore size. The method realizes effective regulation of pore size by changing the type of surfactant and controlling the ratio of solvent and surfactant; specifically, lanthanum chloride is dissolved in water, the surfactant is dissolved in solvent, and the two solutions are mixed to obtain a gel solution, which reacts at a certain temperature, and is filtered, dried, and calcined at high temperature to obtain a mesoporous alumina nanopowder with adjustable pore structure.

[0007] However, the above existing methods all achieve the regulation of the pore structure by introducing a template or a surfactant, and the flexibility of the regulation is poor, and the high diffusion and mass transfer performance of the carrier is not achieved.

[0008] Therefore, there is a need to provide a method that can effectively control the pore size of pseudo-boehmite and improve the diffusion and mass transfer performance by only changing limited reaction conditions without adding any template, surfactant and pore expander, so as to expand the application range of pseudo-boehmite. Summary of the invention

[0009] In order to solve the above technical problems, the purpose of the present invention is to provide a pseudo-boehmite and a preparation method thereof and a γ-alumina carrier with high diffusion and mass transfer performance. The pore structure of the γ-alumina (γ-Al2O3) carrier prepared by the method has high control flexibility, thereby meeting the carrier requirements of different catalytic reactions and having outstanding pore permeability and diffusion performance.

[0010] To achieve the above object, the present invention provides a method for preparing pseudo-boehmite, wherein the preparation method comprises:

[0011] (1) preheating the aluminum-containing acidic solution, the sodium aluminate solution and the reaction bottom water to the gelling reaction temperature respectively; under stirring, dropping the first part of the aluminum-containing acidic solution and the first part of the sodium aluminate solution into the reaction bottom water, controlling the pH value of the gelling reaction to be 5.0-8.5, and mixing uniformly to obtain a material slurry;

[0012] Wherein, based on the total volume of the aluminum-containing acidic solution and the sodium aluminate solution being 100%, the total amount of the first part of the aluminum-containing acidic solution and the first part of the sodium aluminate solution added is 5 vol%-40 vol%, and the amount of the reaction bottom water used is 5 vol%-30 vol%;

[0013] (2) adding the remaining aluminum-containing acidic solution and the remaining sodium aluminate solution dropwise to the material slurry to fully perform a gelling reaction to obtain a reaction slurry;

[0014] (3) The reaction slurry is subjected to step-by-step temperature aging, and after suction filtration, washing, and drying, pseudo-boehmite is obtained.

[0015] According to a specific embodiment of the present invention, preferably, the dripping speed of the first part of the aluminum-containing acidic solution is 10-40mL / min; the dripping speed of the remaining aluminum-containing acidic solution is 50-80mL / min; wherein, during the two additions, the dripping speed of the sodium aluminate solution is automatically adjusted by the reaction device according to the pH value of the gelation reaction set as needed, so that the pH value of the gelation reaction is stabilized at the set value; thereby controlling the dosage ratio of the aluminum-containing acidic solution and the sodium aluminate solution during the two drops. More preferably, the dripping speed of the first part of the aluminum-containing acidic solution is 20-30mL / min; the dripping speed of the remaining aluminum-containing acidic solution is 60-70mL / min; the reaction device for controlling the dripping speed is a PID system, which can be automatically adjusted according to the set neutralization pH value.

[0016] According to a specific embodiment of the present invention, preferably, the concentration of the aluminum-containing acidic solution is 3-9 g / 100 mL, more preferably 3.5-6.5 g / 100 mL, calculated as Al2O3.

[0017] According to a specific embodiment of the present invention, preferably, the aluminum-containing acidic solution includes one or a combination of two or more of an aluminum sulfate solution, an aluminum acetate solution, an aluminum chloride solution, an aluminum oxalate solution, and the like.

[0018] According to a specific embodiment of the present invention, preferably, the concentration of the sodium aluminate solution is 10-28 g / 100 mL, more preferably 16-22 g / 100 mL, calculated as Al2O3.

[0019] According to a specific embodiment of the present invention, preferably, the temperature of the gelling reaction is 30-70°C, more preferably 35-65°C.

[0020] According to a specific embodiment of the present invention, preferably, the reaction bottom water includes one or a combination of two or more of deionized water, a polyol aqueous solution, a polyhydroxy sugar acid aqueous solution, etc.

[0021] According to a specific embodiment of the present invention, preferably, based on the mass of the dry basis of pseudo-boehmite as 100%, the amount of polyol introduced into the reaction bottom water is 0.5wt%-3.5wt%, more preferably 0.8wt%-2.7wt%; the amount of polyhydroxy sugar acid introduced into the reaction bottom water is 0.5wt%-3.5wt%, more preferably 0.8wt%-2.7wt%.

[0022] According to a specific embodiment of the present invention, preferably, the polyol includes one or a combination of two or more of ribitol, glycerol, ethylene glycol, etc.; the polyhydroxy sugar acid includes one or a combination of two or more of gluconic acid, citric acid, malic acid, etc. In the present invention, the introduction of polyols and polyhydroxy sugar acids is mainly to enhance the interaction between particles, thereby improving the stability of pseudo-boehmite particles and making the regulating effect of gelling pH more significant; under a stable gelling system, the gelling pH can play a decisive role in the pore construction of pseudo-boehmite particles, making the regulation of its pores more precise and flexible, and further improving the permeability of the pores of the alumina carrier and enhancing the diffusion capacity.

[0023] According to a specific embodiment of the present invention, preferably, the conditions of the step-by-step temperature-variable aging are: the temperature of the first step aging is the same as the gelling reaction temperature, and the first step aging time is 10-40 min (preferably 20-30 min); the temperature of the second step aging is 60-90°C (preferably 70-85°C), and the second step aging time is 0.5-6h (preferably 1-3h).

[0024] According to a specific embodiment of the present invention, preferably, the temperature of the second aging step is 10-45°C higher than the temperature of the first aging step, more preferably 15-35°C. In the present invention, the first aging step is a static aging process, in which the temperature and pH after the gelling reaction are kept unchanged, and the generation of aluminum hydroxyl groups in the system is promoted by the static stage, so that the frequency of the polycondensation reaction between aluminum hydroxyl groups is increased, thereby improving the stability of the particles and promoting the effective accumulation of pseudo-boehmite particles into pores.

[0025] In some specific embodiments, preferably, the total amount of the first part of the aluminum-containing acidic solution and the first part of the sodium metaaluminate solution added is 20 vol%-30 vol%.

[0026] In some specific embodiments, preferably, the process of dripping the aluminum-containing acid solution and the sodium metaaluminate solution in two batches is carried out in the form of parallel dripping. In the present invention, the purpose of the preheating operation before the first parallel dripping and the parallel dripping in two batches is to configure a stable base liquid so that the subsequent gelation reaction can be carried out in a stable system; on the one hand, it can prevent the pH from fluctuating too much and avoid serious effects on the physicochemical properties of the product; on the other hand, the rate of the hydrolysis reaction can be slowed down in a stable system, which is conducive to the formation of crystal nuclei and the growth of particles, and helps the particles to effectively accumulate into pores and increase the specific surface area. In addition, parallel dripping can simplify the operation process, reduce the operation steps and time, help improve production efficiency, and reduce production costs.

[0027] In some specific embodiments, preferably, in step (1), the mixing time is 3-30 min, more preferably 8-25 min.

[0028] In some specific embodiments, preferably, in step (1), the stirring speed is 50-150 r / min, more preferably 80-120 r / min.

[0029] In some specific embodiments, preferably, the filtration and washing process is repeated 1-4 times, more preferably 2-3 times; the temperature of the deionized water used for washing is 30-80°C, more preferably 50-70°C.

[0030] In some specific embodiments, preferably, the drying temperature is 70-140° C., and the drying time is 3-10 h; more preferably, the drying temperature is 90-120° C., and the drying time is 4-8 h.

[0031] In the above preparation method, preferably, the preparation method specifically comprises the following steps:

[0032] Add reaction bottom water to the neutralization tank of the continuous gelling device, adjust the temperature of the reaction system, and preheat the prepared aluminum-containing acidic solution and sodium aluminate solution in a water bath to the reaction temperature; under the setting program of the flow controller of the continuous gelling device, the aluminum-containing acidic solution and the sodium aluminate solution are quantitatively injected into the neutralization tank of the reactor in batches through a peristaltic pump, and the pH value fluctuation of the gelling system is controlled within the range of ±0.1; after the gelling stage, keep the original reaction conditions unchanged, age and stabilize for a period of time, and then perform variable temperature aging; after the aging, the reaction slurry is filtered, and then the filter cake obtained by filtration is put into a washing tank, and deionized water is added for pulping and washing, and the filtration and washing process are repeated three times; finally, the washed filter cake is placed in a constant temperature drying oven for drying to obtain pseudo-boehmite powder.

[0033] The present invention also provides a pseudo-boehmite, which is prepared by the above preparation method.

[0034] A gamma-alumina carrier with high diffusion and mass transfer performance is obtained by calcining the pseudo-boehmite. The gamma-alumina (gamma-Al2O3) carrier has adjustable pores and excellent mass transfer and diffusion performance.

[0035] According to a specific embodiment of the present invention, preferably, the average pore size of the γ-alumina carrier is 4-20 nm (preferably 11.3-14.2 nm), and the specific surface area is 250-400 m 2 / g (preferably 322-396m 2 / g), pore volume is 0.45-1.38cm 3 / g (preferably 0.99-1.38cm 3 / g).

[0036] According to a specific embodiment of the present invention, preferably, the calcination temperature is 500-700° C., and the calcination time is 2-4 hours; more preferably, the calcination temperature is 550-650° C., and the calcination time is 2.5-3.5 hours.

[0037] The γ-Al2O3 carrier with high diffusion and mass transfer performance prepared in the present invention can be used for preparing a hydroprocessing catalyst.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] (1) The preparation method of pseudo-boehmite provided by the present invention adopts the double aluminum method with low production cost, simple production operation flow and less pollution to synthesize pseudo-boehmite. Without adding any template, surfactant or pore expander, pseudo-boehmite with controllable pore structure can be obtained only through specific preparation steps and control of the colloid pH, and further a γ-Al2O3 carrier with a target pore structure can be obtained, which breaks the problem of poor flexibility of pore adjustment and excessive pH fluctuation during acid-base co-precipitation in the traditional double aluminum method; further, it can overcome the limitation of pore size to meet the needs of different industrial catalysts, increase the functionality of the prepared γ-Al2O3 carrier, and expand the scope of application.

[0040] (2) The high diffusion and mass transfer performance γ-alumina carrier provided by the present invention greatly improves the diffusion and mass transfer performance of the carrier, has good pore permeability, and can achieve diffusion performance that cannot be achieved under conventional preparation conditions, so that the reactant molecules can diffuse rapidly and evenly to the active sites of the catalyst; furthermore, when applied in the field of catalysis, it can increase the rate of the catalytic reaction, increase the selectivity of the reaction, and make the catalytic process more efficient and precise, thereby effectively reducing the diffusion resistance of the reactants and products and improving the activity of the catalytic reaction.

[0041] (3) The preparation method of pseudo-boehmite provided by the present invention can further fine-tune the grain growth of pseudo-boehmite by introducing polyols and polyhydroxy sugar acids, thereby making the pore structure of the γ-Al2O3 carrier more flexible and accurate, providing a guarantee for matching catalysts with different pore requirements; at the same time, the permeability of the pores of the alumina carrier can be further improved, thereby enhancing the diffusion and mass transfer capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 ] are SEM images of pseudo-boehmite prepared in Example 1 (left) and Example 3 (right).

[0043] Figure 2 The pore size distribution of the γ-Al2O3 carrier prepared in Example 1 and Example 3.

[0044] Figure 3 This is the pore size distribution of the γ-Al2O3 carrier prepared in Comparative Example 1-2.

[0045] Figure 4 This is the ZLC test curve of the γ-Al2O3 carrier prepared in Example 1.

[0046] Figure 5 This is the ZLC test curve of the γ-Al2O3 carrier prepared in Comparative Example 1.

[0047] Figure 6 This is the ZLC test curve of the γ-Al2O3 support prepared in Example 3.

[0048] Figure 7 This is the ZLC test curve of the γ-Al2O3 carrier prepared in Comparative Example 2.

[0049] Figure 8 This is the ZLC test curve of the γ-Al2O3 support prepared in Example 5. DETAILED DESCRIPTION

[0050] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.

[0051] Embodiment 1:

[0052] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-alumina (γ-Al2O3) carrier with high diffusion and mass transfer performance, which specifically includes the following steps:

[0053] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 4.0 g / 100 mL, a sodium aluminate solution with a concentration of 20 g / 100 mL, and reaction bottom water (deionized water) are pretreated in a water bath and heated to 60°C; under stirring at 150 r / min, the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution are slowly added dropwise to the reaction bottom water in parallel, and the pH value of the gelling reaction is controlled to be 6.0; the two raw materials are uniformly mixed for 15 minutes to obtain a stable material slurry; based on the sum of the total volume of the aluminum sulfate solution and the sodium aluminate solution as 100%, the total amount of the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution added is 20 vol%, and the amount of the reaction bottom water used is 10 vol%.

[0054] (2) Continue to add the remaining aluminum sulfate solution and sodium aluminate solution to the stable material slurry in parallel, so that the gelling reaction can fully occur and obtain a reaction slurry.

[0055] (3) The reaction slurry was subjected to step-by-step temperature aging. The conditions were maintained the same as those for the gelling reaction, and the slurry was aged at 60°C for 25 min. The temperature was then raised (at a rate of 3°C / min) to 80°C for 1.5 h. After the aging, the slurry was filtered and then washed with 50°C deionized water. The process was repeated three times to obtain a pseudo-boehmite wet cake with impurities removed. The pseudo-boehmite powder was obtained by drying at 120°C for 5 h.

[0056] (4) The pseudo-boehmite powder was calcined at 600°C for 3 hours to obtain a γ-Al2O3 carrier, denoted as S1. The pore structure properties of the carrier are shown in Table 1.

[0057] Embodiment 2:

[0058] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier with high diffusion mass transfer performance, which specifically includes the following steps:

[0059] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 4.5 g / 100 mL, a sodium aluminate solution with a concentration of 18 g / 100 mL, and reaction bottom water (deionized water) are heated in a water bath to 50°C; under stirring at 100 r / min, the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution are slowly added dropwise to the reaction bottom water in parallel, and the pH value of the gelation reaction is controlled to be 7.0; the two raw materials are uniformly mixed for 20 minutes to obtain a stable material slurry; based on the sum of the total volume of the aluminum sulfate solution and the sodium aluminate solution as 100%, the total amount of the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution added is 15 vol%, and the amount of the reaction bottom water used is 15 vol%.

[0060] (2) Continue to add the remaining aluminum sulfate solution and sodium aluminate solution to the stable material slurry in parallel, so that the gelling reaction can fully occur and obtain a reaction slurry.

[0061] (3) The reaction slurry was subjected to step-by-step temperature aging. The conditions were maintained the same as those for the gelling reaction, and the slurry was aged at 50°C for 30 min. The temperature was then raised to 70°C (heating rate 3°C / min) for 1 h. After the aging, the slurry was filtered and then washed with 60°C deionized water. This process was repeated twice to obtain a pseudo-boehmite wet cake with impurities removed. The pseudo-boehmite powder was obtained by drying at 110°C for 6 h.

[0062] (4) The pseudo-boehmite powder was calcined at 600°C for 3.5 hours to obtain a γ-Al2O3 carrier, denoted as S2. The pore structure properties of the carrier are shown in Table 1.

[0063] Embodiment 3:

[0064] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier with high diffusion mass transfer performance, which specifically includes the following steps:

[0065] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 5.5 g / 100 mL, a sodium aluminate solution with a concentration of 25 g / 100 mL, and reaction bottom water (deionized water) are heated in a water bath to 65°C; under stirring at 100 r / min, the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution are slowly added dropwise to the reaction bottom water in parallel, and the pH value of the gelation reaction is controlled to be 8.0; the two raw materials are uniformly mixed for 20 minutes to obtain a stable material slurry; based on the sum of the total volume of the aluminum sulfate solution and the sodium aluminate solution as 100%, the total amount of the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution added is 25 vol%, and the amount of the reaction bottom water used is 5 vol%.

[0066] (2) Continue to add the remaining aluminum sulfate solution and sodium aluminate solution to the stable material slurry in parallel, so that the gelling reaction can fully occur and obtain a reaction slurry.

[0067] (3) The reaction slurry was subjected to step-by-step temperature aging. The conditions were maintained the same as those for the gelling reaction, and the slurry was aged at 65°C for 35 min. The temperature was then raised (at a rate of 3°C / min) to 80°C for 2 h. After the aging, the slurry was filtered and then washed with 50°C deionized water. This process was repeated three times to obtain a pseudo-boehmite wet cake with impurities removed. The pseudo-boehmite powder was obtained by drying at 110°C for 6 h.

[0068] (4) The pseudo-boehmite powder was calcined at 600°C for 2.5 hours to obtain a γ-Al2O3 carrier, denoted as S3. The pore structure properties of the carrier are shown in Table 1.

[0069] Embodiment 4:

[0070] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier with high diffusion mass transfer performance, which specifically includes the following steps:

[0071] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 4.7 g / 100 mL, a sodium aluminate solution with a concentration of 22 g / 100 mL, and reaction bottom water (deionized water) are heated in a water bath to 55°C; under stirring at 150 r / min, the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution are slowly added dropwise to the reaction bottom water in parallel, and the pH value of the gelation reaction is controlled to be 7.5; the two raw materials are uniformly mixed for 20 minutes to obtain a stable material slurry; based on the sum of the total volume of the aluminum sulfate solution and the sodium aluminate solution as 100%, the total amount of the first part of the aluminum sulfate solution and the first part of the sodium aluminate solution added is 10 vol%, and the amount of the reaction bottom water used is 8 vol%.

[0072] (2) Continue to add the remaining aluminum sulfate solution and sodium aluminate solution to the stable material slurry in parallel, so that the gelling reaction can fully occur and obtain a reaction slurry.

[0073] (3) The reaction slurry was subjected to step-by-step temperature aging. The conditions were maintained the same as those for the gelling reaction, and the slurry was aged at 55°C for 35 min. The temperature was then raised to 75°C (heating rate 3°C / min) for 1.5 h. After the aging, the slurry was filtered and then washed with 55°C deionized water. This process was repeated twice to obtain a pseudo-boehmite wet cake with impurities removed. The pseudo-boehmite powder was obtained by drying at 110°C for 6 h.

[0074] (4) The pseudo-boehmite powder was calcined at 600°C for 3 hours to obtain a γ-Al2O3 carrier, denoted as S4. The pore structure properties of the carrier are shown in Table 1.

[0075] Embodiment 5:

[0076] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier with high diffusion and mass transfer performance. The preparation method is basically the same as the process of preparing pseudo-boehmite in Example 1, with the only difference being that: the bottom water of the reaction is an aqueous solution of ribitol, and the amount of ribitol introduced is 1.8wt% based on the mass of the dry basis of the pseudo-boehmite as 100%; the ribitol is stirred until it is completely dissolved, and then the pseudo-boehmite powder is obtained by referring to the steps and proportions for preparing the pseudo-boehmite in Example 1. The pseudo-boehmite powder is calcined at 600°C for 3 hours to obtain a γ-Al2O3 carrier, denoted as S5, and its pore structure properties are shown in Table 1.

[0077] Embodiment 6:

[0078] This embodiment provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier with high diffusion mass transfer performance. The preparation method is basically the same as the process of preparing pseudo-boehmite in Example 1, with the only difference being that: the bottom water of the reaction is an aqueous solution of glycerol, and the amount of glycerol introduced is 1.2wt% based on the mass of the dry basis of pseudo-boehmite as 100%; the glycerol is stirred until it is completely dissolved, and then the pseudo-boehmite powder is obtained by referring to the steps and proportions for preparing pseudo-boehmite in Example 1. The pseudo-boehmite powder is calcined at 600°C for 3 hours to obtain a γ-Al2O3 carrier, denoted as S6, and its pore structure properties are shown in Table 1.

[0079] Comparative Example 1:

[0080] This comparative example provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier, which specifically comprises the following steps:

[0081] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 4.0 g / 100 mL and a sodium aluminate solution with a concentration of 20 g / 100 mL are added dropwise to reaction bottom water (deionized water) in parallel, heated to 60°C, and the pH value of the gelation reaction is controlled to be 6.0 to carry out a gelation reaction; based on the sum of the total volumes of the aluminum sulfate solution and the sodium aluminate solution being 100%, the amount of the reaction bottom water used is 10 vol%.

[0082] (2) After the gelling reaction is completed, the mixture is aged at 60°C for 25 minutes, and then the temperature is raised (heating rate 3°C / min) to 80°C for 1.5 hours. After the aging, the obtained slurry is filtered and then washed with 50°C deionized water, which is repeated three times. The pseudo-boehmite wet cake with impurities removed is obtained. The pseudo-boehmite powder is obtained by calcining the pseudo-boehmite powder at 600°C for 3 hours to obtain a γ-Al2O3 carrier, which is denoted as DS1. Its pore structure properties are shown in Table 1.

[0083] Comparative Example 2:

[0084] This comparative example provides a pseudo-boehmite and a preparation method thereof and a γ-Al2O3 carrier, which specifically comprises the following steps:

[0085] (1) Based on Al2O3, an aluminum sulfate solution with a concentration of 4.0 g / 100 mL and a sodium aluminate solution with a concentration of 20 g / 100 mL are added dropwise to reaction bottom water (deionized water) in parallel, heated to 60°C, and the pH value of the gelation reaction is controlled to be 8.0 to carry out a gelation reaction; based on the sum of the total volumes of the aluminum sulfate solution and the sodium aluminate solution being 100%, the amount of the reaction bottom water used is 5 vol%.

[0086] (2) After the gelling reaction is completed, the mixture is aged at 60°C for 25 minutes, and then the temperature is raised (heating rate 3°C / min) to 80°C for 1.5 hours. After the aging, the obtained slurry is filtered and then washed with 50°C deionized water, which is repeated three times. The pseudo-boehmite wet cake with impurities removed is obtained. The pseudo-boehmite powder is obtained by calcining the pseudo-boehmite powder at 600°C for 2.5 hours to obtain a γ-Al2O3 carrier, which is denoted as DS2. Its pore structure properties are shown in Table 1.

[0087] In catalytic hydrogenation reactions, mass transfer diffusion capacity has an important influence on the efficiency, selectivity and catalyst life of the reaction. The mass transfer diffusion capacity is closely related to the physical and chemical properties of the carrier. For example, the specific surface area, surface roughness and surface chemical properties of the carrier will affect the mass transfer diffusion process; among these factors, the pore structure of the carrier has a particularly prominent influence on its mass transfer diffusion capacity.

[0088] The pore structure of the γ-Al2O3 carrier prepared in Examples 1-6 and Comparative Examples 1-2 is explored as follows:

[0089] Table 1. Pore structure parameters of γ-Al2O3 carrier

[0090] sample Gelation pH <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Average pore size (nm) S1 6.0 383 1.33 14.0 S2 7.0 329 0.99 12.0 S3 8.0 322 1.05 11.3 S4 7.5 336 1.09 12.8 S5 6.0 396 1.38 14.2 S6 6.0 388 1.34 13.6 DS1 6.0 358 1.21 13.1 DS2 8.0 296 0.87 10.5

[0091] Table 1 records the pore structure parameters of the γ-Al2O3 carriers prepared in Examples 1-6 and Comparative Examples 1-2. It can be seen from Table 1 that, without adding any template agent and surfactant, Examples 1-6 can achieve flexible regulation of the pseudo-boehmite pore structure by only water bath pretreatment, batch cocurrent feeding, regulating the pH of the gelling reaction, and changing the aging conditions, and obtain the pore volume and pore diameter of the γ-Al2O3 carrier required for the target application. In addition, Figure 1 The SEM images of the pseudo-boehmite prepared in Example 1 (left) and Example 3 (right) are shown, verifying that the pore structures of the pseudo-boehmite prepared under different gelling and neutralization conditions are significantly different. When the pH of the gelling reaction is the same, the γ-Al2O3 carrier prepared by the method provided in the embodiment of the present invention has a larger specific surface area than the traditional method of the comparative example.

[0092] Figure 2 , Figure 3 The pore size distribution when adjusting the pH of the gel is shown in the method provided by the embodiment of the present invention and the traditional method of the comparative example. Figure 2 , Figure 3 It can be seen that although the pore structure of the γ-Al2O3 carrier has a certain degree of change under different gelation and pH in the traditional synthesis method (Comparative Example 1, Comparative Example 2), the adjustment flexibility of this method is poor and it is impossible to achieve a rapid and flexible conversion from a broad pore size distribution to a concentrated pore size distribution.

[0093] However Figure 2 In Example 1 and Example 3, the pore size distribution can be flexibly adjusted by changing the gelation and neutralization pH to obtain γ-Al2O3 carriers with wide pore size distribution and concentrated pore size distribution; wherein, the wide pore size distribution can accommodate molecules of different sizes, and is suitable for processing complex mixtures or catalytic reactions requiring multiple active sites; and the γ-Al2O3 carrier with concentrated pore size distribution, due to its uniform pore size, is conducive to the diffusion and transmission of specific molecules, has good diffusion performance, and can promote the improvement of the selectivity and efficiency of the catalytic reaction.

[0094] Reasonable pore distribution and size design can provide more mass transfer channels, reduce mass transfer resistance, and thus accelerate the diffusion rate of reactant molecules. This not only helps to improve catalytic activity, but also prolongs the service life of the catalyst and reduces catalyst deactivation caused by poor mass transfer.

[0095] For substrates with large molecular weight, the limitation of mass transfer diffusion is particularly obvious. Enhancing the mass transfer capacity may even be the key to the success of the experiment. Therefore, when researching and developing new hydrogenation catalysts, full attention should be paid to and the mass transfer diffusion performance of the carrier should be optimized to improve the overall effect of the catalytic reaction.

[0096] The diffusion properties of the γ-Al2O3 carriers prepared in Example 1, Example 3, Example 5 and Comparative Examples 1-2 are investigated as follows:

[0097] The diffusion rate of the γ-Al2O3 carrier was measured by the zero length column (ZLC) technique, and the desorption curve and fitting curve of the γ-Al2O3 carrier were obtained. The different curves of each sample respectively represent the desorption time t corresponding to the sample when the concentration of trimethylbenzene is desorbed to near the baseline under different temperature conditions. C / C0 represents the change in concentration, that is, the ratio of the real-time concentration to the initial concentration.

[0098] Figure 4 and Figure 5 The comparison shows the trimethylbenzene desorption curves and the corresponding fitting curves of sample S1 and sample DS1. Figure 4 , Figure 5 It can be clearly observed that when trimethylbenzene is desorbed to a relative concentration of 0.01, under the conditions of water bath pretreatment, batch and parallel dripping of raw materials, and step-by-step temperature aging in Example 1, the desorption time required for sample S1 is significantly shorter than the desorption time required for sample DS1 with the same gelling pH, indicating that sample S1 prepared by the method of the present invention has better diffusion performance.

[0099] Similarly, Figure 6 and Figure 7 The comparison shows the trimethylbenzene desorption curves and the corresponding fitting curves of sample S3 and sample DS2. Figure 6 , Figure 7 It can be clearly observed that when trimethylbenzene is desorbed to a relative concentration of 0.01, under the control of water bath pretreatment, batch and parallel dripping of raw materials, and step-by-step temperature aging in Example 3, the desorption time required for sample S3 is significantly shorter than the desorption time required for sample DS2 with the same gelling pH, indicating that sample S3 prepared by the method of the present invention has better diffusion performance.

[0100] Figure 8 The trimethylbenzene desorption curve and the corresponding fitting curve of the sample S5 obtained when the aqueous solution of ribitol was used as the reaction bottom water are shown. Figure 8 It can be seen that when trimethylbenzene is desorbed to a relative concentration of 0.01 and the gelation pH is the same, sample S5 requires a shorter desorption time and has a higher specific surface area, which indicates that the introduction of polyhydroxy sugars / alcohols makes the regulating effect of the gelation pH more significant and further improves the diffusion performance of the γ-Al2O3 carrier.

[0101] By measuring the concentration change curve of the adsorbate over time during the above desorption process, the desorption kinetic information is obtained, and then the diffusion coefficient D / R is obtained by model fitting. 2; According to the Arrhenius formula, the activation energy Ea required for diffusion can be calculated, and the results are shown in Table 2.

[0102] Table 2. Sample diffusion characterization results

[0103]

[0104]

[0105] It can be clearly observed from Table 2 that when the gelling pH is the same, the D / R of samples S1 and S3 synthesized in Example 1 and Example 3 under different temperature conditions is 2 The values ​​are greater than those of samples DS1 and DS2 prepared by conventional synthesis in comparative examples 1-2; at the same time, the activation energy Ea required for diffusion is also lower than that of conventional methods. For the same sample, as the temperature increases, D / R 2 The value also increases accordingly, indicating that the mass transfer diffusivity of the γ-Al2O3 carrier increases with increasing temperature.

[0106] Therefore, when preparing pseudo-boehmite, the present invention increases the permeability of the pores of the γ-Al2O3 carrier by regulating the process of preheating treatment, batch parallel flow feeding, step-by-step temperature aging, etc., so that its diffusion performance is greatly superior to the traditional synthesis method, so that when the γ-Al2O3 carrier is used in the catalytic field, it can effectively reduce the diffusion resistance of reactants and products.

[0107] In addition, after adding ribitol, the D / R of sample S5 at different temperature conditions was 2 The values ​​of D / R of sample S5 are slightly larger than those of sample S1 with the same gelation pH and have a lower required diffusion activation energy Ea, which indicates that the addition of polyhydroxy sugar / alcohol can further improve the permeability of the γ-Al2O3 carrier pores and enhance the diffusion capacity. 2 The value is the highest, and it has excellent diffusion and mass transfer capabilities.

Claims

1. A method for preparing pseudo-boehmite, wherein: The preparation method comprises: (1) preheating the aluminum-containing acidic solution, the sodium aluminate solution and the reaction bottom water to the gelling reaction temperature respectively; under stirring, dropping the first part of the aluminum-containing acidic solution and the first part of the sodium aluminate solution into the reaction bottom water, controlling the pH value of the gelling reaction to be 5.0-8.5, and mixing uniformly to obtain a material slurry; Wherein, based on the total volume of the aluminum-containing acidic solution and the sodium aluminate solution being 100%, the total amount of the first part of the aluminum-containing acidic solution and the first part of the sodium aluminate solution added is 5 vol%-40 vol%, and the amount of the reaction bottom water used is 5 vol%-30 vol%; (2) adding the remaining aluminum-containing acidic solution and the remaining sodium aluminate solution dropwise to the material slurry to fully perform a gelling reaction to obtain a reaction slurry; (3) The reaction slurry is subjected to step-by-step temperature aging, and after suction filtration, washing, and drying, pseudo-boehmite is obtained.

2. The preparation method according to claim 1, wherein The first portion of the aluminum-containing acidic solution is added at a rate of 10-40 mL / min; the remaining portion of the aluminum-containing acidic solution is added at a rate of 50-80 mL / min; During the two additions, the dropping speed of the sodium aluminate solution is automatically adjusted by the reaction device so that the pH value of the gelling reaction is stabilized at a set value.

3. The preparation method according to claim 1, wherein The concentration of the aluminum-containing acidic solution is 3-9 g / 100 mL in terms of Al2O3; Preferably, the aluminum-containing acidic solution includes one or a combination of two or more of an aluminum sulfate solution, an aluminum acetate solution, an aluminum chloride solution, and an aluminum oxalate solution.

4. The preparation method according to claim 1, wherein Calculated as Al2O3, the concentration of the sodium aluminate solution is 10-28 g / 100 mL.

5. The preparation method according to claim 1, wherein The temperature of the gelling reaction is 30-70°C.

6. The preparation method according to claim 1, wherein The reaction bottom water includes one or a combination of two or more of deionized water, polyol aqueous solution, and polyhydroxy sugar acid aqueous solution; Preferably, based on 100% of the dry mass of pseudo-boehmite, the amount of polyol introduced into the reaction bottom water is 0.5wt%-3.5wt%; the amount of polyhydroxy sugar acid introduced into the reaction bottom water is 0.5wt%-3.5wt%.

7. The preparation method according to claim 6, wherein: The polyol includes one or a combination of two or more of ribitol, glycerol, and ethylene glycol; The polyhydroxy sugar acid includes one or a combination of two or more of gluconic acid, citric acid and malic acid.

8. The preparation method according to claim 1, wherein The conditions of the step-by-step temperature aging are as follows: the temperature of the first step aging is the same as the gelling reaction temperature, and the time of the first step aging is 10-40 minutes; The second aging temperature is 60-90°C, and the second aging time is 0.5-6h; Preferably, the temperature of the second aging step is 10-45°C higher than the temperature of the first aging step.

9. Pseudo-boehmite, prepared by the preparation method according to any one of claims 1 to 8.

10. A γ-alumina carrier with high diffusion and mass transfer performance, which is obtained by calcining the pseudo-boehmite according to claim 9; Preferably, the average pore size of the γ-alumina carrier is 4-20 nm, and the specific surface area is 250-400 m 2 / g, pore volume is 0.45-1.38cm 3 / g.

Citation Information

Patent Citations

  • Preparation of pore diameter adjustable mesoporous powdered alumina

    CN101412527B

  • Preparation method for aperture-adjustable alumina oxide

    CN102173442B

Cited By

  • Pseudo-boehmite and preparation method thereof

    CN121107443A

  • A pseudo-boehmite and a method for producing the same

    CN121107443B